2017
DOI: 10.3389/fnbeh.2017.00173
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dual-Hemisphere Transcranial Direct Current Stimulation Over the Parietal Operculum on Tactile Orientation Discrimination

Abstract: The parietal operculum (PO) often shows ipsilateral activation during tactile object perception in neuroimaging experiments. However, the relative contribution of the PO to tactile judgment remains unclear. Here, we examined the effect of transcranial direct current stimulation (tDCS) over bilateral PO to test the relative contributions of the ipsilateral PO to tactile object processing. Ten healthy adults participated in this study, which had a double-blind, sham-controlled, cross-over design. Participants di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 69 publications
2
20
0
Order By: Relevance
“…This suggests an increased inhibition of sensory processing from the opposite side of the body in preference for efficient processing of sensory inputs on the tDCS stimulated side. Recent studies investigating unilateral and dual-hemisphere tDCS effects on the S1 and S2 further support this notion of opposite side interhemispheric inhibition of tactile processing (Fujimoto et al 2014(Fujimoto et al , 2017. With respect to sensory detection threshold levels, the mean detection thresholds obtained in this study for both high and low frequency vibrations were comparable to results reported by Morley and Rowe (1990) that had an identical VDT testing procedure.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This suggests an increased inhibition of sensory processing from the opposite side of the body in preference for efficient processing of sensory inputs on the tDCS stimulated side. Recent studies investigating unilateral and dual-hemisphere tDCS effects on the S1 and S2 further support this notion of opposite side interhemispheric inhibition of tactile processing (Fujimoto et al 2014(Fujimoto et al , 2017. With respect to sensory detection threshold levels, the mean detection thresholds obtained in this study for both high and low frequency vibrations were comparable to results reported by Morley and Rowe (1990) that had an identical VDT testing procedure.…”
Section: Discussionsupporting
confidence: 83%
“…The amplitude thresholds for detecting a 30Hz vibration are however much higher than for 200Hz, where the Pacinian channels could influence detection of the 30Hz stimuli since the threshold functions of different channels are quite close at this frequency (Gescheider et al 2002). Fujimoto et al (2017) however displayed through electric field monitoring of tDCS over the S2 with 25cm electrodes that a contributing stimulation of S1 could not be ruled out. It is therefore likely that our use of 35cm 2 electrodes over the S1 also contributed to stimulation of the S2 and possibly influencing both low and high frequency VDT processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it could be argued that tDCS duration and current intensity or density were insufficient for modulating PO excitability. This could be reasonably excluded, as Fujimoto et al (2017) obtained significant differences in tactile orientation discrimination when applying tDCS over PO, with the same current intensity but a 2.5 times smaller current density and for a duration 5-minute shorter than in our work. Moreover, if one takes into account the electric field simulations published by Fujimoto in the same paper, it is apparent that 2 mA tDCS is more than sufficient to alter the electric potential over the area of interest.…”
Section: Discussionmentioning
confidence: 49%
“…In this aim, we modulated coPO excitability by using anodal and cathodal transcranial Direct Current Stimulation (tDCS), a technique which has been proved to selectively interfere with the excitability of many cortical structures involved in motor and cognitive processes (for a review see Brunoni et al, 2013), including PO (Fujimoto et al, 2017). Notably, the applied currents are usually sufficiently low to grant a focal stimulation but nevertheless they produced long-lasting effects in many cases (Brunoni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%